MAJOR COMPONENT AND ANTIMICROBIAL ACTIVITY OF THE EXTRACT OF BITTER LEAF (Vernonia amydalina) AGAINST Vibrio parahaemolyticus - Van Nhan Le; Quang Minh Bui; Viet Anh Le; Van Diep Le; Thi Thanh Mai Nguyen; Hung Manh Nguyen; Cong Thuong Phi; Van Tien Tran; Thi Quynh Bui; Hai Anh Tran; Thi Oanh Doan; Nguyen Khang La (Journal of Animal and Plant Sciences, 2025)
It is an undeniable fact that natural bioactive compounds extracted from diverse plants and herbs have attracted significant public attention and scientific interest due to their health-promoting benefits as antioxidants and antimicrobial agents. In this research, the main phytochemical compositions of V. amygdalina leaves were determined by Gas chromatography–mass spectometry (GC-MS). There were 18 groups detected from the methanol extract of V. amygdalina leaves, in which, fatty acids were the major component (55.29%), followed by the ketone group at 10.44%. Phenol and terpenoid compounds comprised 6.19% and 5.13% respectively, ranking third and fourth in abundance. The antibacterial properties of the extract from V. amygdalina leaves were evaluated against V. parahaemolyticus which caused Acute hepatopancreatic necrosis disease (AHPND) in Whiteleg shrimp (Liptopenaeus vannamei). The antibacterial zone diameters of the leaf extract ranged from 9.5 mm to 19.0 mm during 72 hours of the inhibition, corresponding to the concentration of V. amygdalina changed from 200 mg.mL-1 to 500 mg.mL-1. This illustrates the potential application of V. amygdalina leaf extracts as the supply food or used to produce bio-preparations for preventing and controlling the growth of V. parahaemolyticus in shrimp culture industry.
Keywords: Vernonia amygdalina; Vibrio parahaemolyticus; AHPND; Liptopenaeus vannamei; antimicrobial activity